Estimation of impact of RPE65-mediated inherited retinal disease on quality of life and the potential benefits of gene therapy. Issue 11 (18th January 2019) - Lloyd, Andrew; Piglowska, Natalia; Ciulla, Thomas; Pitluck, Sarah; Johnson, Scott; Buessing, Marric; O'Connell, Thomas
Abstract : Background/aims: In rare diseases, health-related quality of life (HRQL) data can be difficult to capture. Given the ultrarare nature of RPE65 -mediated inherited retinal disease (IRD), it was not feasible to recruit a patient sample and collect HRQL data prospectively. The objectives of this study were to develop health state descriptions of RPE65 -mediated IRD, and to estimate associated patient utilities. Methods: Vignette descriptions of IRD states were developed and then assessed to elicit utilities. The vignettes ranged from moderate vision loss through to hand motion to no light perception (NLP). Six retina specialists with additional expertise in IRDs provided a proxy valuation of the vignettes using generic measures of health—the 5-level version of EQ-5D-5L and Health Utility Index 3 (HUI3). The data were then scored using standard methods for each instrument. Results: Weights from both HRQL measures revealed a large decline in scores with vision loss. The EQ-5D-5L weights ranged from 0.709 for moderate vision loss to 0.152 for hand motion to NLP. The HUI3 weights ranged from 0.519 to − 0.039, respectively. A decline was seen on both measures, and the degree of decline from moderate vision loss to NLP was identical on both (−0.56). Conclusion: This is the first study to report HRQL weights (or utilities) for health states describing different levels of vision loss in patients with IRD, specifically those with RPE65 -mediated disease. The parallel decline in scores from the EQ-5D and HUI3 corroborates the substantial impact of progressive vision loss on HRQL.